Implementation of The Complete Systematic Land Registration Program (PTSL) Based on Community Participation (Study in Uaranggantung Village, Lumajang Regency) - Maulana, Ilham; Poernomo, Djoko; Wahyudi, Edy (Raudhah Publisher, 2024)
The complete systematic land registration program (PTSL) is a strategic step of the government in encouraging complete land administration. Lumajang Regency since 2018 has been one of the districts selected as the implementer of the PTSL program. The researcher emphasizes the research locus of Uranggantung Village. The village was selected as the target of the PTSL program in 2024. The realization of targets that are not achieved from a public program/policy (PTSL) is a problem that must be overcome. The purpose of this study is to describe the implementation of the complete sitematic land registration program (PTSL) in Uranggantung Village, Lumajang Regency. This study uses a descriptive qualitative research approach. The results of the study show that the implementation of the PTSL program in the form of community participation in Uranggantung Village contains several stages, namely the decision-making stage, the implementation stage, the benefit taking stage, and the evaluation stage. In addition, this study describes the implementation of the PTSL program through environmental conditions, inter-organizational relationships, resources, and characteristic implementing agencies.